Lack of an Effect of Ritonavir Alone and Lopinavir‐Ritonavir on the Pharmacokinetics of Fenofibric Acid in Healthy Volunteers. Issue 1 (January 2016) - Gordon, Lori A.; Malati, Christine Y.; Hadigan, Colleen; McLaughlin, Mary; Alfaro, Raul M.; Calderón, Mónica M.; Kovacs, Joseph A.; Penzak, Scott R.
Abstract : Study Objective: Because we previously observed a significant 41% reduction in gemfibrozil exposure after 2 weeks of lopinavir‐ritonavir administration, we sought to determine the influence of lopinavir‐ritonavir and ritonavir alone on the pharmacokinetics of fenofibric acid, an alternative to gemfibrozil for the treatment of elevated triglyceride levels. Design: Open‐label, single‐sequence pharmacokinetic study. Setting: Clinical Research Center at the National Institutes of Health. Subjects: Thirteen healthy adult volunteers. Intervention: Subjects received a single oral dose of fenofibrate 145 mg during three study phases: before ritonavir administration, after 2 weeks of administration of ritonavir 100 mg twice/day, and after 2 weeks of administration of lopinavir 400 mg–ritonavir 100 mg twice/day. Measurements and Main Results: Serial blood samples were collected over 120 hours for determination of fenofibric acid concentrations. Fenofibric acid pharmacokinetic parameter values were compared before and after concomitant ritonavir or lopinavir‐ritonavir administration. The geometric mean ratios (90% confidence intervals) for fenofibric acid area under the plasma concentration–time curve were 0.89 (0.77–1.01) after 14 days of ritonavir alone compared with baseline (p>0.05) and 0.87 (0.69–1.05) after 14 days of lopinavir‐ritonavir compared with baseline (p>0.05). Study drugs were generally well tolerated; all adverse events were mild or moderate, transient, and resolved without intervention. Conclusion: In contrast to a significant interaction between gemfibrozil and lopinavir‐ritonavir, neither lopinavir‐ritonavir nor ritonavir alone altered the pharmacokinetics of fenofibric acid in healthy volunteers. These data suggest that fenofibrate remains an important option in human immunodeficiency virus–infected patients receiving common ritonavir‐boosted therapy.